TRAINING ON THE USE OF LETTER FILING INFORMATION SYSTEMS FOR VOCATIONAL HIGH SCHOOL STUDENTS - Rima Tamara Aldisa; Moh. Iwan Wahyuddin (Adisam Publisher, 2024)
This service research aims to explore the effectiveness of training in the use of letter archiving information systems for Vocational High School students. In today's digital era, skills in managing information and documentation electronically have become very important, especially in educational and professional environments. Therefore, this training program is designed to equip students with practical knowledge and skills in the use of mail archiving information systems, which are key components in modern administrative management. This research methodology uses a qualitative approach with a focus on evaluating training effectiveness through pre-test and post-test, as well as observation and in-depth interviews with participants. The training was carried out in several sessions which included a basic introduction to archiving information systems, practical use of the software, as well as effective archiving techniques and strategies. The research results showed that there was an increase in students' understanding and skills regarding the use of letter archiving information systems after attending the training. Students demonstrate the ability to manage and archive documents electronically, which indicates the potential for increased efficiency and productivity in school administration activities as well as in preparation for the future work environment. In addition, positive feedback from students indicated that this training was successful in increasing their awareness of the importance of good and professional information management.